Life cycle costing (LCC) comparison between conventional and new type of composite doctor blade - Laitiainen, Timo (2016)
Since the paper industry is an energy-intensive and using lots of all kinds of raw mate- rials for the production, the need for more sustainable products in the paper industry is increasing and highly appreciated. In this thesis one of the commodity products used in the paper machine, doctor blades were studied. Two different kinds of doctor blades, conventional and a new type of composite blade Royal R1 100, were selected. The purpose of this thesis was to compare and evaluate these doctor blades from a life cycle perspective and to find out the most cost-efficient and more environmentally friendly product. The Life cycle costing (LCC) analysis is a method, which summarizes all the costs asso- ciated with the life cycle of the product and was chosen for this comparison. The analysis was done for both of the doctor blades, where life cycle inventory was di- vided into four different phases: production, transportation, use and end of use. The results of this LCC analysis showed, that one of the four phases played a key role. The use phase was for both of the doctor blades biggest factor and the outcome was very similar to the other LCC analysis done before. As a total result of this analysis, new type of doctor blade, Royal R1 100 is the preferable type of the doctor blade being more cost efficient and environmentally friendly product.